The Relationship Between Laboratory Learning and Nursing Students' Self-Confidence During Preceptorship - Rika Endah Nurhidayah; Erniyati; Reisy Tane; Cholina Trisa Siregar (Caring: Indonesian Journal of Nursing Science, 2026)
The gap between classroom knowledge and clinical practice remains a problem in nursing professional education. This gap creates a fear of making mistakes and a lack of self-confidence in nursing students. Laboratory learning is expected to be a solution that makes students more confident in providing health care. This correlational research design aims to analyze the relationship between laboratory learning and nursing students' self-confidence during clinical practice. The population in this study were all final-year students of the Faculty of Nursing, University of North Sumatra, totaling 196 students. The sample size was determined using the Slovin formula with α=0.05, resulting in a sample size of 132 students. The sample was selected randomly. The instrument used was developed based on theory, then validity and reliability tests were conducted to ensure its content was appropriate and suitable for use. The research data were analyzed using Spearman correlation due to the non-normal distribution of the data. The results of the data analysis showed a significant relationship between laboratory learning and student self-confidence. The coefficient value was positive (+0.417), which means that the better the laboratory learning, the higher the students' self-confidence, with a moderate strength of relationship. Keyword: Laboratory Learning, Nursing Students' Self-Confidence, Preceptorship